Performance of Kinnow mandarin as influenced by longevity of rootstocks (Indian Journal of Arid Horticulture, 2017)
Rootstocks are known to influence bearing behavior, tree vigor, yield, fruit quality, and tolerance to adverse conditions (Castle and Krezdom, 1977; Syvertsen, 1981; Castle et al., 1988; Wutscher, 1989). The challenge of replanting old citrus soils with young trees can be partially addressed by selecting appropriate rootstocks. Additionally, the performance and adaptability of fruit trees can vary significantly depending on the type of rootstock and the agroclimatic conditions of the area. Over time, a tree may become unproductive on a particular site. Thus, the economic longevity of a commercial orchard heavily relies on the choice of promising rootstocks.
Keywords: selecting appropriate; rootstocks